Creativity of High School Teachers Over Time - Kharchenko, Leonid N.; Aybatirov, Kazbek S.; Aybatirova, Muslimat A.; Gladchenko, Viktoria E.; Kharlanova, Natalja N. (International Journal of Criminology and Sociology, 2022)
This article deals with the creativity of teachers of higher education in the process of their professional activity. The teacher's creativity is substantiated as an important factor that determines the success of the teacher's professional activity and, as a consequence, a better educational process. An active professional thesaurus of a teacher is considered as a means of supporting indicators of changes in biological creativity. The data were obtained from direct surveys of teachers, administrators and managers of universities, using D. Johnson's creativity questionnaire, adapted by E.V. Tunik, as well as from the review of the results of scientific and pedagogical activities of university teachers: original articles, creative classes, and translation of creative behavior. Based on the data of the study, the dependence of the level of creativity of a higher education teacher on the level of a professional thesaurus is revealed. In particular, the article presents the level of creativity of teachers who combine educational work with research, teachers who are mainly engaged in educational activities and representatives of the administrative and managerial personnel of universities, combining managerial functions with teaching.